MEDIATION EFFECT OF VALUE ADDED INTELLECTUAL CAPITAL (VAIC) IN CORPORATE GOVERNANCE (CG) AND FINANCIAL PERFORMANCE RELATIONS - Kartika Hendra Titisari (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2018)
This study aims to examine the relationship of Corporate Governance and Financial Performance with Intellectual Capital as a mediating variable with a sample of companies included in the chemical industry sector basis and the period of 2012 - 2014. The sampling method used in this research is purposive sampling. The data analysis procedures, structural equation modeling (SEM) with PLS Warp 4.0. The test results showed Corporate Governance affect the ROA. The greater the Corporate Governance further enhance the financial accountability of the company. Corporate Governance does not affect the Intellectual capital. Intellectual Capital affects the financial performance. Value added intellectual capital plays an important role in the performance of financial support the use of physical assets (fixed) to contribute to the company's performance. Although the model fit, but the results of the analysis of intellectual capital does not mediate the relationship Corporate Governance and Financial Performance. Suggestions for further research can be done in other sectors. It is quite possible in the banking sector, as it has done in several countries where the corporate governance affect the Intellectual capital.